Autorzy:Dubiecka-Kruk Barbara, Dubiecka Anna, Bazyluk Anna
Wydawnictwo:WSiP
Rok wydania:2014
Oblicz 2^-2+3^-14.43 gwiazdek na podstawie 7 opinii

`a)\ 2^-2+3^-1=1/2^2+1/3=1/4+1/3=3/12+4/12=7/12` 

`b)\ 3^-1+3^-2+3^-3=1/3+1/3^2+1/3^3=1/3+1/9+1/27=9/27+3/27+1/27=13/27` 

`c)\ (1/2)^-1+(1/2)^-2+(1/2)^-3=2^1+2^2+2^3=2+4+8=14`  

`d)\ 3^-3*(1/3)^-2+4^-3:(1/2)^3=(1/3)^3*(1/3)^-2+4^-3:2^-3=` 

`\ \ \ =(1/3)^(3+(-2))+(4:2)^-3=(1/3)^1+2^-3=1/3+1/2^3=` 

`\ \ \ =1/3+1/8=8/24+3/24=11/24` 

`e)\ 5^2+(-1/3)^-4-2^5+(0,1)^-2=25+(-3)^4-32+(1/10)^-2=` 

`\ \ \ =25+81-32+10^2=74+100=174` 

`f)\ 4^4*4^-2+6^5*6^-3-8^-2:(-1/2)^4=4^(4+(-2))+6^(5+(-3))-1/8^2:1/16=` 

`\ \ \ =4^2+6^2-1/64*16/1=16+36-1/4=52-1/4=51 3/4`